Reshaping sport performers' careers: Lessons from the 2023–2024 war in Israel - Roy David Samuel; Yair Galily; Gershon Tenenbaum (Asian Journal of Sport and Exercise Psychology)
The war experience (WE) presents a highly troublesome period for sport performers, with severe effects on their lives and career trajectories. In this article, we initially conceptualize the WE through the scheme of change for sport psychology practice (Samuel & Tenenbaum, 2011a). The WE is considered a longitudinal, multifaceted, unpredicted, noncontrolled, negative change-event, developed over four distinct stages with specific demands and responses: (a) a pre-war stage, (b) War stage-A accompanied by instability and confusion, (c) War stage-B characterized by active coping or regression, and (d) War stage-C; return to sport activity, modification of activity, or retirement. The development of this change process in sport performers’ careers is discussed within the context of the 2023 Israel-Hamas war. Thereafter, we discuss applied practice efforts to support sport performers through the WE. The conclusions offer future avenues for researchers and practitioners when attempting to evaluate and cope with this unique change-event.